The Role of Social Media in Digital Marketing of Children’s Products and the Impact of Digital Marketing Strategies on Families’ Tendency to Purchase Products - Arif, Dalal Ahmed (The Arab Journal of Administration, 2025)
The current study aims to identify the role of social media in the digital marketing of children’s products and knowing the impact of digital marketing strategies on the family’s tendency to buy products,and identifying the impact of digital marketing strategies (e-mails posts, search engine, social networks, YouTube videos) on the family’s tendency to buy children’s products, The research used the descriptive analytical method, and the questionnaire was also used to collect information and data from members of the research sample, which was randomly selected from the research community consisting of Saudi families, the selected sample reached the selected sample amounted to (224) individual, the results of the statistical analysis showed some results, The results of the statistical analysis showed that there is an impact of digital marketing strategies through (e-mails, blog posts, search engine, social networks, YouTube videos) on families’ tendency to buy children’s products to a large extent. The results also showed that the media that had the most influence on digital marketing strategies in families’ orientation toward purchasing children’s products were social networking sites, followed by the search engine, then YouTube videos, then blog posts, and in last place came e-mail messages. The study recommended the need to pay attention to social media because of its role in the digital marketing of children’s products, and the need for increased attention on the part of software companies to factors related to marketing via social media that have an impact on digital marketing performance.